Finn at the Festival. - GRAHAM, ANTHONY (Quadrant Magazine, 2023)
The article focuses on Finn, a rural journalist, who reflects on his life as he writes articles and books about farming. It explores his unexpected invitation to be a presenter at the Palmerville Writers Festival in South Australia, raising questions about the value of his work and his place in the literary world.